Comparative prospective study of biofeedback therapy and neuromuscular electrical stimulation in rehabilitation of patients with pelvic ﬂoor dysfunctions - V. A. Krutova; A. V. Nadtochy (Сеченовский вестник)
Aim. To evaluate the eﬀectiveness of the combined eﬀects of biological feedback (BFB therapy) and electroimpulse stimulation (EIS) in rehabilitation of patients with pelvic ﬂoor dysfunctions. Materials and methods. A comparative prospective study included 235 women with clinical and ultrasound signs of genital prolapse stages I-IV according to POP-Q. The observation program was completed by 209 patients who were divided into group 1 with stage I-II prolapse and group 2 with stage III-IV prolapse. Vaginal extraperitoneal vaginopexy with installation of mesh implant was performed in group 2 patients before inclusion in the study. Lifestyle modiﬁcation was recommended for all patients. In each group, patients were divided into subgroups of control and treatment (BOS-therapy and EIS). Group 1: subgroup A - control (n=47), subgroup B - treatment (n=56); group 2: subgroup C - control (n=49), subgroup D - treatment (n=57). Index of inﬂuence on the quality of life (IQOLI) and parameters of ultrasound were evaluated.Results. After a year of observation, in subgroup A, the IQOLI decreased by 5%, in subgroup B by 64% ( p< 0.05); in subgroup C, IQOLI decreased by 32%, in subgroup D - by 63% of the initial value ( p